Problems of preservation at the Neolithic lakeside settlements at Lake Burgäschi, Switzerland. A case study of the effects of an artificial lowering of the lake level in 1943 - Hostettler, Marco; Hafner, Albert (Acta Geographica Lodziensia, 2020)
This paper describes recently observed severe preservation problems at the Neolithic lakeside settlement of Aeschi SO, Burgäschisee, Nord. The site is located on Lake Burgäschi, a small water body of late-glacial origin in Central Switzerland. Since an artificial lake lowering in 1943 and draining of the site, the originally waterlogged sediments have been increasingly drying out. Recent fieldwork on the site (2015–17) and its evaluation gave the opportunity to directly assess the actual preservation status of the archaeological site. The excavations show that the archaeological remains are affected by mechanical destruction caused by draining cracks and fissures and tree-uprooting, which have mixed parts of the stratigraphic sequences. Additionally, the organic matter is heavily deteriorated and most organic artefacts and environmental data are lost forever. The comparison of the newly obtained observations with older excavation data and neighbouring sites confirms a high loss of archaeological information. Even though there exist examples for successful rewetting and insitu conservation of archaeological wetland sites, for the site of Aeschi SO, Burgäschisee, Nord the most reasonable measure to undertake seems to be a rescue excavation.